No tan lines - Angell, Kate (Kensington Publishing Corp., 2012)
"There's a place where the ocean meets the shores, where kicking off your shoes and baring some skin is as natural as sneaking under the boardwalk for an ice cream cone and stolen kisses. But life isn't all a beach for Shaye Cates, even if her idea of an office is a shady umbrella at the water's edge equipped with cell phone and laptop. Steely-eyed Trace Saunders is the incredibly irksome fly in her coconut tanning oil. And running a kids' softball team with her longtime rival is going to have everyone in her little Florida town buzzing. Her scads of laid-back relatives and his whole uptight clan know that Shaye just wants to play ball while Trace thinks only of business. But beneath the twinkling lights of the ferris wheel, the magic of sea and sand can sweep away every inhibition ... Suddenly, it's summertime, and the lovin' is easy."--p. [4] of cover.